Building Social Capital in Uganda: The Role of NGOs in Mitigating HIV/AIDS Challenges - Jamil, Ishtiaq; Muriisa, Roberts (ISTR (International Society for third Sector Rearch), 2004)
Social Capital is an important explanatory variable for performance of different nation states as well as improved livelihoods of people in different countries. The paper explores the process by which social capital is created and sustained to cope with HIV/AIDS challenges in Uganda. We argued that building social capital matters for the work against HIV/AIDS. Social capital makes a difference in lives of those living with HIV/AIDS. The paper focuses on the stock of cooperation (solidarity and social networks) among members, beneficiaries and or clients of NGOs and documents how cooperation is utilised to impact HIV/AIDS challenges; HIV transmission and spread, increased mortality and stress, social exclusion and stigma. We argue that, while a number of NGOs are engaged in HIV/AIDS related activities, only those that have focused on developing social relations among people living with HIV/AIDS have had greater impacts. We make an assertion that NGOs that have focused on empowering their members through bringing them into regular contacts have had an important contribution to their lives.
Building Social Capital: Mitigating the Challenges of HIV/AIDS
Social Capital is an important explanatory variable for performance of different nation states as well as improved livelihoods of people in different countrie
Keywords: Social Capital, Solidarity, Civil society.